Sensitizing brain metastases to stereotactic radiosurgery using hyperbaric oxygen: A proof-of-principle study. (December 2022) - Hartford, Alan C.; Gill, Gobind S.; Ravi, Divya; Tosteson, Tor D.; Li, Zhongze; Russo, Gregory; Eskey, Clifford J.; Jarvis, Lesley A.; Simmons, Nathan E.; Evans, Linton T.; Williams, Benjamin B.; Gladstone, David J.; et al.
Highlights: HBO may be successfully administered within 15 minutes prior to SRS delivery. HBO combined with SRS for brain metastases showed no excess toxicity. Clinical outcomes trended favorably for HBO with SRS (but not significant). Phase II trial of pre-op SRS will study cellular & clinical effects of adding HBO. Abstract: Purpose: Increased oxygen levels may enhance the radiosensitivity of brain metastases treated with stereotactic radiosurgery (SRS). This project administered hyperbaric oxygen (HBO) prior to SRS to assess feasibility, safety, and response. Methods: 38 patients were studied, 19 with 25 brain metastases treated with HBO prior to SRS, and 19 historical controls with 27 metastases, matched for histology, GPA, resection status, and lesion size. Outcomes included time from HBO to SRS, quality-of-life (QOL) measures, local control, distant (brain) metastases, radionecrosis, and overall survival. Results: The average time from HBO chamber to SRS beam-on was 8.3 ± 1.7 minutes. Solicited adverse events (AEs) were comparable between HBO and control patients; no grade III or IV serious AEs were observed. Radionecrosis-free survival (RNFS), radionecrosis-free survival before whole-brain radiation therapy (WBRT) (RNBWFS), local recurrence-free survival before WBRT (LRBWFS), distant recurrence-free survival before WBRT (DRBWFS), and overall survival (OS) were not significantly different for HBO patients and controls on Kaplan-Meier analysis, though at 1-year estimated survival rates trended in favor of SRS + HBO: RNFS – 83% vs 60%; RNBWFS – 78% vs 60%; LRBWFS – 95% vs 78%; DRBWFS – 61% vs 57%; and OS – 73% vs 56%. Multivariate Cox models indicated no significant association between HBO treatment and hazards of RN, local or distant recurrence, or mortality; however, these did show statistically significant associations (p < 0.05) for: local recurrence with higher volume, radionecrosis with tumor resection, overall survival with resection, and overall survival with higher GPA. Conclusion: Addition of HBO to SRS for brain metastases is feasible without evident decrement in radiation necrosis and other clinical outcomes.